Angiolymphoid Hyperplasia with Eosinophilia Developing in a 9 Year Old Patient with History of Tuberculosis - Kaler, Amrit Kaur; BJ, Naveen Kumar (International Journal of Innovative Research in Medical Science, 2017)
Angiolymphoid hyperplasia with eosinophilia (ALHE) is a rare benign reactive vasoproliferative disease, presenting as painless vascular papules or nodules in the dermal and subcutaneous tissue particularly in the head and neck region. The etiology is uncertain whether; reactive or neoplastic; but its association with Tuberculosis is rare and very few cases have been reported so far. We present a nine year old girl with a swelling on the dorsum of foot since 3 months. She reported to have taken treatment for Tuberculosis when she was six years. Excisional biopsy showed vascular proliferation with prominent mixed inflammatory component, diagnosed as ALHE based on histopathological and Immunohistochemical methods. Its association in the present case showed possibly a result of complex immunological mechanism secondary to chronic infection like tuberculosis. We present a case of ALHE with a very rare presentation on the dorsum of the foot in a 9 year old female with a history of Tuberculosis.